Photodynamic Therapy for Esophageal cancer - R Lambert (Canadian Journal of Gastroenterology)
In photodynamic therapy, a photosensitizing drug is injected and then activated by light in the red spectral region to produce reactive, highly toxic singlet oxygen, which causes cell tissue and damage. When the distinction between tumoral and normal tissue is difficult at endoscopy, photodynamic therapy is preferable to any other conservative method of destruction. The main indications comprise genital, head and neck, bronchial, bladder and gastrointestinal tumours, particularly esophageal cancer (including squamous cell cancer and glandular neoplasia). Esophageal tumours should be class T1 or T2, at most, and detected at endoscopy. Dysplasia which is flat, sessile and multicentric may also be an indication for photodynamic therapy. Advanced esophageal cancers are contraindicated for photodynamic therapy.